2010
DOI: 10.1103/physrevb.81.233405
|View full text |Cite
|
Sign up to set email alerts
|

Impurity-induced states on the surface of three-dimensional topological insulators

Abstract: We calculate the modification of the local electronic structure caused by a single local impurity on the surface of a 3D Topological Insulator. We find that the LDOS around the Dirac point of the electronic spectrum at the surface is significantly disrupted near the impurity by the creation of low-energy resonance state(s) -however, this is not sufficient to (locally) destroy the Dirac point. We also calculate the non-trivial spin textures created near the magnetic impurities and discover anisotropic RKKY coup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

20
299
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(320 citation statements)
references
References 22 publications
20
299
1
Order By: Relevance
“…Theoretical results for non-magnetic impurities using a continuum model for the Dirac surface state have indeed shown on both absence of backscattering 4 , as also confirmed experimentally, 5 and how these impurities never destroy, even locally, the low-energy spectrum, including the Dirac point. 6 This is in contrast to magnetic impurities, which have theoretically been shown to open a gap in the surface spectrum. 7 Taken together, these results make TIs intriguing candidates for both spintronic devices and topological quantum computation.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Theoretical results for non-magnetic impurities using a continuum model for the Dirac surface state have indeed shown on both absence of backscattering 4 , as also confirmed experimentally, 5 and how these impurities never destroy, even locally, the low-energy spectrum, including the Dirac point. 6 This is in contrast to magnetic impurities, which have theoretically been shown to open a gap in the surface spectrum. 7 Taken together, these results make TIs intriguing candidates for both spintronic devices and topological quantum computation.…”
mentioning
confidence: 98%
“…Thus, for the dilute impurity case n → ∞, we expect a single resonance peak to be present in the low-energy spectrum, contrary to 2D surface state continuum model results. 6 We attribute this difference to the 3D dimensionality of the problem. In Fig.…”
mentioning
confidence: 99%
“…It has been suggested that the interaction between magnetic impurities and the topological state can cause an opening of an energy gap at the Dirac point (DP), provided that the magnetic order is oriented normal to the surface plane [5][6][7]. Nevertheless, the stability of the TSS against local magnetic perturbations is currently under heavy debate [8][9][10], since little is known about the fundamental interface effects of magnetic entities with TI surfaces as well as the static magnetic properties of impurities in these materials.In this work we present a comprehensive study of the magnetic properties of iron impurities on a prototypical TI Bi 2 Se 3 using local scanning tunneling microscopy (STM) and integral x-ray magnetic circular dichroism (XMCD) techniques. We show that the multiplet structure visible in x-ray absorption spectra reflect a high-spin state of the adsorbed Fe impurities, which are confirmed to bind at hollow sites of the surface lattice, under the influence of trigonal crystal fields given in hollow site positions of the Bi 2 Se 3 surface.…”
mentioning
confidence: 99%
“…It has been suggested that the interaction between magnetic impurities and the topological state can cause an opening of an energy gap at the Dirac point (DP), provided that the magnetic order is oriented normal to the surface plane [5][6][7]. Nevertheless, the stability of the TSS against local magnetic perturbations is currently under heavy debate [8][9][10], since little is known about the fundamental interface effects of magnetic entities with TI surfaces as well as the static magnetic properties of impurities in these materials.…”
mentioning
confidence: 99%
“…If the chemical potential μ is finely tuned at the conical point of the spectrum of the SS, the effective interaction between two local moments at a distance r apart monotonically decays as r −3 and the magnetic phase diagram (Curie temperature versus concentration of magnetic moments) can be qualitatively obtained within a mean-field approach. 5 However, when μ falls within the band, a serious problem arises to identify the FM region in the phase diagram, 6 due to the appearance of an oscillating contribution to the interaction with slowly varying amplitude 7 (∼r −2 ) that makes the mean-field approach problematic. Recently, 8 a description was proposed, which treats the local moments at a mean-field level, in the case when these are localized in deep levels, but cannot describe the situation when the TM atoms form shallow levels near the conical point of the spectrum and are rather delocalized.…”
mentioning
confidence: 99%